The impact of second generation succession on family business innovation and performance - Li, Jiajia (2021)
Family owned businesses are omnipresent and numerically dominant across the world and have played an acknowledged role in creating jobs, generating tax revenue and driving technological innovation. Their health and growth are critical to almost every nation’s economic well being. Yet they are now faced with the incoming of a huge succession tide over the next ten to twenty years and exposed to ever increasing challenges that require more up to date succession and governance. Facing both opportunities and threats that are emerging from the world of VUCA, how will family owned companies stay innovative and competitive through intergenerational succession. With this question in mind, the study examines the influence of second generation succession on family business innovation and performance. It further investigates the moderating effect of CEO duality on the relation between second generation succession and family business innovation. The empirical evidence from Chinese A share listed family firms indicates that the transfer of leadership responsibility from actual controller of the founding generation to family member of the second generation restrains family business innovation. And this negative relation between second generation succession and family business innovation is stronger in the presence of CEO duality, where second generation successors taking concurrent position of chairman and general manager. The study also finds that family firms have better firm performance after second generation successors take over the leadership. The observations are consistent with the established hypotheses, and the empirical results are steady and robust. Based on the findings, the study proposes several recommendations, such as establishing formal succession planning and preparation, encouraging successors’ entrepreneurship and adopting a CEO nonduality leadership structure. The empirical evidence and practical recommendations help family businesses to promote succession process smoothly and achieve continuous innovation and sustainable development in the succession process.